Anterior Inferior Tibiofibular Ligament Suture Tape Augmentation for Isolated Syndesmotic Injuries. (July 2022) - Jamieson, Marissa D.; Stake, Ingrid Kvello; Brady, Alex W.; Brown, Justin; Tanghe, Kira K.; Douglass, Brenton W.; Clanton, Thomas O.
Background: The best operative construct and technique for treatment of isolated syndesmotic injuries is highly debated. The purpose of this study was to determine whether the addition of anterior inferior tibiofibular ligament (AITFL) suture repair or suture tape (ST) augmentation provides any biomechanical advantage to the operative repair of an isolated syndesmotic injury. Methods: Twelve lower leg specimens underwent biomechanical testing in 6 states: (1) intact, (2) AITFL suture repair, (3) AITFL suture repair + transsyndesmotic suture button (SB), (4) AITFL suture repair + ST augmentation + SB, (5) AITFL suture repair + ST augmentation, and (6) complete syndesmotic injury. The ankle joint was subjected to 6 cycles of 5 Nm internal and external rotation torque under a constant axial load. The spatial relationship between the tibia, fibula, and talus was continuously recorded with a 5-camera motion capture system. Results: AITFL suture repair and AITFL suture repair + ST augmentation showed no statistically significant change in fibula kinematics compared to the intact state. Compared to native, AITFL suture repair + SB showed increased fibular external rotation (+2.32 degrees, P < .001), and decreased tibiofibular gap (overtightening) (–0.72 mm, P = .007). AITFL suture repair + ST augmentation + SB also showed increased fibular external rotation (+1.46 degrees, P = .013). Sagittal plane motion of the fibula was not significantly different between any states. None of the repairs restored intact state talus rotation; however, the repairs that used ST augmentation reduced the talus external rotation laxity compared to the complete syndesmotic injury. Conclusion: AITFL suture repair and AITFL ST augmentation best restored the rotational kinematics and stability of the fibula and ankle joint in an isolated syndesmotic injury model. Clinical Relevance: AITFL suture repair with or without ST augmentation may be a good operative addition or alternative to SB fixation for isolated syndesmotic disruptions.